1989
DOI: 10.3109/00365548909021685
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Year Survey of Drug Resistance in Aerobic and Anaerobic Fecal Bacteria of Surgical Inpatients: Clinical Relevance and Relation to Local Antibiotic Consumption

Abstract: One-day studies of bacteriological cultures of fecal specimens obtained from 409 surgical inpatients at 5 occasions enabled rapid assessment of antibiotic resistance in aerobic and anaerobic bacteria, relevant to abdominal infection. This novel approach to surveillance of drug resistance was tested in a 7-year survey at a surgical department. A distinct correlation between local drug consumption and prevalence of resistant fecal bacteria was recorded for ampicillin and doxycycline. 17 other agents studied show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…B. thetaiotaomicron and B. ovatus were the most commonly isolated members of the B. fragilis group. In previous studies, B. ovatus and then B. fragilis were the most frequently isolated anaerobic resistant strains from intestinal microfloras (1,12). The antimicrobial susceptibility of the B. fragilis group in the present study correlates well with those found in recent investigations in Canada and Europe (12,16).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…B. thetaiotaomicron and B. ovatus were the most commonly isolated members of the B. fragilis group. In previous studies, B. ovatus and then B. fragilis were the most frequently isolated anaerobic resistant strains from intestinal microfloras (1,12). The antimicrobial susceptibility of the B. fragilis group in the present study correlates well with those found in recent investigations in Canada and Europe (12,16).…”
Section: Discussionsupporting
confidence: 89%
“…In the outpatient group, one-third of the resistant strains made up more than 1% of the total anaerobic microflora, while in both hospitalized groups, two-thirds of the resistant strains constituted more than 1% of the total anaerobic fecal flora. Strains from the B. fragilis group were isolated most frequently, as has been reported previously (1,3,12). B. thetaiotaomicron and B. ovatus were the most commonly isolated members of the B. fragilis group.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations